Evaluation of pediatric patient's age, behaviors, and reasons for the first dental visit in edirne, turkey : a cross-sectional study = Evaluación de la edad, los comportamientos y las razones de la primera visita dental del paciente pediátrico en Edirne, Turquía : un estudio transversal - Ozveren, Neslihan
Oral and dental health are vital parts of general baby health, and early dental visits provide significant prevention-focused intervention and parental counseling regarding oral health. Evaluating the age and main complaints of children is therefore important during their first dental visit (FDV). The purposes of this study were to determine the age, reason for the visit, behavioral response, and caries status at the FDV and to evaluate the factors affecting these parameters. Parents of 325 pediatric patients (159 males; 166 females; mean age 7.20±2.78 years) at their FDV were asked to fill out a questionnaire requesting sociodemographic information and their child's medical history, brushing habits, and reasons for attending dental consultation. The decayed-missing-filled-teeth (dmft/DMFT) scores were also recorded. The child's behavioral responses during the FDV were evaluated according to Frankl's Behavior Rating Scale (FBRS). Higher maternal education level and dmft/DMFT score were associated with earlier FDV age. The most common reason for the FDV was dental caries in 33.5% of patients, followed by toothache (29.5%). Most of the children showed positive behavior (46.7%), with positive behavior affected by age and negative behavior affected by the dmft/DMFT score and distance from home. The mean dmft/DMFT score was 8.1±4.4 and was negatively affected by toothbrushing frequency and family income. These study results indicate that Turkish children living in Edirne present at a late age for the FDV. Raising awareness in terms of dental health care among parents is important to ensure that children attend their FDV at an early age.